The Allocation and Impact of Social Funds : Spending on School Infrastructure in Peru - Paxson, Christina; Schady, Norbert R. (Washington, DC: World Bank, 2014)
Between 1992 and 1998 the Peruvian Social Fund (foncodes) spent about US dollar 570 million funding micro projects throughout the country. Many of these projects involved constructing and renovating school facilities. This article uses data from foncodes, the 1993 population census in Peru, and a 1996 household survey conducted by the Peruvian Statistical Institute to analyze the targeting and impact of foncodes investments in education. A number of descriptive and econometric techniques are employed, including nonparametric regressions, differences in differences, and instrumental variables estimators. Results show that foncodes investments in school infrastructure have reached poor districts and poor households within those districts. The investments also appear to have had positive effects on school attendance rates for young children.